Challenges and possibilities on approaching the nature of the Serra do Espinhaço Meridional from basic education textbooks (Revista Espinhaço, 2023)
Textbooks are the main support used by school teachers, however, they express generalist content and do not show all the diversity that Brazil presents in terms of biodiversity, physical geography and culture. This is a documental research with a qualitative approach that investigated three textbooks of Natural Sciences of the 6th year of Elementary School adopted in public schools in the region of Serra do Espinhaço Meridional, Minas Gerais. The objective was to identify scientific contents in those textbooks that provide an approximation with the context and the life history of students and the nature of Serra do Espinhaço. We identified and discussed the contents and made suggestions so that teachers, when approaching the scientific processes and concepts exposed in the textbooks, explain and exemplify them through themes related to the nature of Serra do Espinhaço. We recognize there are many challenges but overcoming them is necessary to achieve meaningful learning, critical formation and effective engagement of students in solving local socio-environmental problems.
Keywords: Basic education; Curriculum; Serra do Espinhaço; Science learning; Textbook